2019
DOI: 10.1111/jace.16340
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism studies of hydrothermal cold sintering of zinc oxide at near room temperature

Abstract: Zinc oxide densification mechanisms occurring during the cold sintering process (CSP) are examined by investigating specifically the effects of ion concentration in solution, temperature, pressure, and die sealing. The experiments suggest that mass transport through solution is a primary densification mechanism and that either a pre-loaded solution or grain dissolution can supply migrating ions. Additionally, results indicate cold sintering zinc oxide requires a critical pressure value, above which densificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 50 publications
5
38
0
4
Order By: Relevance
“…In addition to the ZnO reflexes, low-intensity reflexes are visible, which, as in [19], belong to the Zn 5 (OH) 8 Cl 2 H 2 O (JCPDS 7-155) phase, formed after TVT ZnO at 240 • C ( Table 3). The appearance of the Zn 5 (OH) 8 Cl 2 H 2 O phase with a decomposition temperature of 250 • C was observed in [34] and also in [10]. On the X-ray pattern of the CSP4 sample (Figure 7b), unidentified traces of the decay product of this phase are marked with a round icon.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to the ZnO reflexes, low-intensity reflexes are visible, which, as in [19], belong to the Zn 5 (OH) 8 Cl 2 H 2 O (JCPDS 7-155) phase, formed after TVT ZnO at 240 • C ( Table 3). The appearance of the Zn 5 (OH) 8 Cl 2 H 2 O phase with a decomposition temperature of 250 • C was observed in [34] and also in [10]. On the X-ray pattern of the CSP4 sample (Figure 7b), unidentified traces of the decay product of this phase are marked with a round icon.…”
Section: Resultsmentioning
confidence: 94%
“…In [6], the CSP of ZnO ceramics was carried out at a temperature of 240 • C in a medium of 20% acetic acid solution (1.6 mol% CH 3 COOH by weight of ZnO). To explain the effect of the acidic medium of an aqueous solution on mass transfer during sintering, the idea of the dissolution of stressed areas and the release of ZnO in the contact region of particles is usually used [7][8][9][10][11][12]. When discussing the results of CSP in several works [7,[13][14][15][16], the insufficiency of the dissolutionreprecipitation mechanism for understanding the processes occurring during sintering of oxides with the participation of water is noted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the type of mineralization agent also has a great influence on the quality and growth rate of the crystal. Studies have shown that the use of acids, such as HCl, H 2 SO 4 , H 3 PO 4 , HNO 3 , and HCOOH, as mineralizers can reduce the crystal growth temperature to below 300 °C, thus allowing the use of relatively simpler autoclaves [51,52]. Tani et al [53] summarized the effect of mineralizers on ZrO 2 crystallization using the hydrothermal method as shown in Table 1.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…By measuring the contact angle (CA) at room temperature, the surface free energy of BaTiO3 powders at room temperature can be determined to qualitatively explain the influence of 80 nm and 200 nm powders on the sintering force. The CA method is often used to measure the contact angle between powder and specific liquid, and then the corresponding surface free energy can be obtained through calculation [33,34] are mixed to form a binary particle size system, the difference of the surface free energy between them is easy to induce self-assembly [35]. According to Owens…”
Section: The Surface Free Energymentioning
confidence: 99%
“…The dispersion force ( d l  ) and the polarity force ( p l  ) of specific liquid are required to test the contact angle of powders, whose specific data are shown in Table Ⅱ [33,34]. are mixed to form a binary particle size system, the difference of the surface free energy between them is easy to induce self-assembly [35]. According to Owens…”
Section: The Surface Free Energymentioning
confidence: 99%